Globalization and U.S. corporate tax policies: evidence from import competition - Chen, Tao (2023)
This paper studies how globalization affects the corporate tax policies of U.S. manufacturing firms. Using U.S.-granting China Permanent Normal Trade Relations as a quasi-natural experiment, we find a significant increase in tax reduction activities for firms facing higher exposure to Chinese imports. The effect is more pronounced for firms with higher managerial slack. We also find that the effect is stronger for firms in less diversified products market and faster changing industries. We also show that U.S. firms facing higher Chinese import competition are more likely to engage in other tax-motivated activities: acquisition of subsidiaries in low-tax regions and suspected transfer pricing. Furthermore, we explore the 2017 tax cut and the recent U.S.-China trade dispute and find that firms engage less in tax reduction activities after the 2017 tax cut and after the tariff increase for Chinese imports.